Willingness to Pay Masyarakat Terhadap Hunian Berbasis Green Architecture - Hafid Achmady Brahmantya; Dewi Larasati; Hanson E Kusuma (Universitas Sebelas Maret Surakarta, 2025)
Sustainable development requires the adoption of green buildings in the housing sector to reduce environmental impact. However, premium costs remain a major barrier, limiting public interest in green housing. Therefore, this study analyzes Willingness to Pay (WTP) as an indicator of value perception and commitment to sustainable architecture. A qualitative descriptive approach with bivariate open coding analysis was applied, utilizing data from online questionnaires with snowball sampling. Findings identify six key factors influencing WTP, with financial behavior as the dominant factor (52%), followed by environmental awareness, perceived benefits, innovation preference, education level, and long-term expectations. The results confirm that economic considerations play a crucial role in determining willingness to pay for green housing, that needs a balanced strategy between cost and benefits is essential to increase adoption of green buildings and support sustainable development.